Efficacy of oral ritodrine treatment versus no treatment following suppression of uterine contractions by intravenous ritodrine in cases of preterm labor - Kumru, Selahattin; Gürates, Bilgin; Parmaksiz, Cem (My University, 2004)
OBJECTIVE: To compare the efficacy of oral ritodrine treatment versus no treatment following suppression of the uterine contractions by intravenous ritodrine in cases of preterm labor (PL). STUDY DESIGN: This study was undertaken in Firat University Medical School, Department of Obstetric and Gynecology between January-December 2003. Thirty-eight patients hospitalized as PL and whose uterine contractions were suppressed by ritodrine, were randomly divided into two groups. The first group (ritodrine IV, n=18) had given no treatment following suppression of uterine contractions while the second group (ritodrine IV+PO, n=20) had given oral ritodrine as the maintenance treatment. All patients were given betamethasone in addition to tocolytics. Time gained from the beginning of the tocolytics to delivery, demographic characteristics of newborns, and APGAR scores were analyzed. Independent samples Student's t test and chi-square tests were used when necessary. The level of statistical significance was set at p<0.05. RESULT(s): Demographic characteristics were similar between the two groups. In the ritodrine IV+PO group, gained time until delivery was significantly longer than that in ritodrine IV group (p<0.05). All of the other parameters were not different between the two groups (p>0.05). CONCLUSION(s): Ritodrine can suppress the uterine contractions in cases of PL. Administering oral ritodrine following intravenous treatment as the maintenance treatment can prolong the time until delivery. However, we were unable to show that oral ritodrine maintenance improves perinatal outcomes. We suggest that larger studies are needed to clarify this issue.
Erken do?um tehdidi olgularinda ritodrinin sadece i?ntravenöz verilmesi ile i?ntravenöz tedaviden sonra oral i?dame uygulamalarinin karşilaştirilmasi
Keywords: Oral Maintenance; Preterm Labor; Ritodrine; Tocolysis